A multifunctional anti-O-Antigen human monoclonal antibody protects against Shigella sonnei infection in vivo - Matteo Ridelfi; Giacomo Vezzani; Emanuele Roscioli; Giampiero Batani; Elena Boero; Francesco Nannini; Eleonora Marini; Ushasi Bhaumik; Girmay Desalegn; Ornella Serpino; Antonio Molinaro; Ida Paciello; et al. (Proceedings of the National Academy of Sciences, 2025)
Shigellosis is a global public health challenge that mostly affects low- and middle-income countries and causes considerable morbidity and mortality among children under 5 y of age. Multi- and extensively drug-resistant Shigella sonnei strains associated with recent outbreaks in high-income countries exacerbate the problem and have prompted the World Health Organization to include Shigella spp. among the high-risk pathogens for which novel prophylactic and therapeutic tools are urgently needed. Among the most promising and cutting-edge solutions, monoclonal antibodies are gaining considerable attention in the infectious diseases field. Here, we report the discovery of human monoclonal antibodies against S. sonnei , a species whose prevalence is constantly increasing worldwide and is associated with frequent drug-resistant infections. We isolated antibodies generated in response to an experimental S. sonnei vaccine followed by a controlled human infection and screened them by using a panel of high-throughput assays. We identified a molecule which exhibited potent bactericidal activity in vitro, inhibition of invasion of epithelial cells and conferred full protection from S. sonnei infection in vivo. Overall, our study provides a candidate antibody that can rapidly progress to industrial development for application as a prophylactic, therapeutic, and diagnostic tool against shigellosis.